Penggunaan Ayat Al-Qur’an Sebagai Media Pengobatan Alternatif: ( Studi Living Al-Qur’an Praktik Ruqyah Di Desa Pamarayan) - Haromain, Imam; Sholahuddin Al Ayubi; Mus’idul Millah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This research examines people's perceptions of the use of verses from the Koran as a form of healing, with a special focus on the practice of ruqyah. This research aims to understand how people view the use of Al-Qur'an verses as an alternative therapeutic method, especially in the context of ruqyah, and identify factors that influence their perception of the effectiveness and validity of this method. The research methods used in this study involved public opinion surveys, interviews, and qualitative analysis of the responses and experiences of individuals who had undergone ruqyah treatment. The research results show that the majority of people have a positive view regarding the use of Al-Qur'an verses as a means of healing, especially in the practice of ruqyah. Society considers ruqyah to be a valid and effective approach in dealing with various health problems, including mental, physical and spiritual disorders. A strong belief in the power of the verses of the Qur'an and their spiritual meaning plays an important role in forming this positive outlook. This research provides valuable insight into people's perceptions of the use of Al-Qur'an verses in the field of healing, especially in the context of ruqyah. The findings of this study provide guidance for health practitioners, researchers, and policy makers to understand and respect community beliefs when designing healing programs based on verses of the Qur'an, thereby increasing the acceptance and effectiveness of this alternative medicine in society